Engineered LINE-1 retrotransposition in nondividing human neurons - Macia, Angela; Widmann, Thomas J.; Heras, Sara R.; Ayllon, Veronica; Sanchez, Laura; Benkaddour-Boumzaouad, Meriem; Muñoz-Lopez, Martin; Rubio, Alejandro; Amador-Cubero, Suyapa; Blanco-Jimenez, Eva; Garcia-Castro, Javier; Menendez, Pablo; et al. (Genome Research, 2017)
Half the human genome is made of transposable elements (TEs), whose ongoing activity continues to impact our genome. LINE-1 (or L1) is an autonomous non-LTR retrotransposon in the human genome, comprising 17% of its genomic mass and containing an average of 80–100 active L1s per average genome that provide a source of inter-individual variation. New LINE-1 insertions are thought to accumulate mostly during human embryogenesis. Surprisingly, the activity of L1s can further impact the somatic human brain genome. However, it is currently unknown whether L1 can retrotranspose in other somatic healthy tissues or if L1 mobilization is restricted to neuronal precursor cells (NPCs) in the human brain. Here, we took advantage of an engineered L1 retrotransposition assay to analyze L1 mobilization rates in human mesenchymal (MSCs) and hematopoietic (HSCs) somatic stem cells. Notably, we have observed that L1 expression and engineered retrotransposition is much lower in both MSCs and HSCs when compared to NPCs. Remarkably, we have further demonstrated for the first time that engineered L1s can retrotranspose efficiently in mature nondividing neuronal cells. Thus, these findings suggest that the degree of somatic mosaicism and the impact of L1 retrotransposition in the human brain is likely much higher than previously thought.